The detection, isolation, characterization, and biological significance of 3-hydroxy-3-methyl-2-oxindole in human urine - Chorn, David J.(David Jonathan) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. in Med. Sc.) -- University of Stellenbosch, 1987.